Kerja-Kerja Pendisiplinan Oleh Guru Agama Islam di Sekolah Menengah Kejuruan: Best Practice di SMK Negeri 1 Pemangkat - Wulandari, Tri; Kurniawan, Syamsul; Lubis, Putri Handayani (LP2M IAIN kUDUS, 2025)
This study explores the role of Islamic religious teachers in cultivating a culture of discipline grounded in Islamic values at SMK Negeri 1 Pemangkat, Sambas Regency. Discipline is understood not merely as the enforcement of rules, but as the shaping of “docile bodies” through pedagogical mechanisms, systematic training, and the internalization of values. Employing a qualitative descriptive design, the research collected data through participant observation, in-depth interviews, and document analysis, applying Miles and Huberman’s interactive model for analysis. The study is framed by Michel Foucault’s concept of disciplinary bodies—entities that are regulated, transformed, and refined through spatial organization, temporal regulation, hierarchical surveillance, and normalization. The findings reveal that Islamic religious teachers fulfill multiple roles: instructor, educator, classroom manager, mentor, guardian of disciplinary culture, and moral exemplar. Strategies employed include daily habituation, structured training programs (e.g., LDDK), personalized communication, and systematic supervision and evaluation. Contributing factors comprise students’ self-awareness, active parental involvement, positive peer models, and collaborative engagement between the school and the wider community. Challenges include limited discipline awareness, insufficient parental oversight, and adverse peer or environmental influences. The study demonstrates that Islamic education fosters disciplined character not through coercion, but via structured regulation, internalization, and exemplary leadership, offering a Foucauldian lens to inform more contextually grounded character education strategies in vocational school settings.